Dual-modal spatiotemporal imaging of ultrafast dynamics in laser-induced periodic surface structures - Qianyi Wei; Jielei Ni; Yuquan Zhang; Yanan Fu; Zhangyu Zhou; Xi Xie; Yixuan Chen; Shuoshuo Zhang; Xiaocong Yuan; Changjun Min (Light: Advanced Manufacturing)
The interactions between ultrafast lasers and materials reveal a range of nonlinear transient phenomena that are crucial in advanced manufacturing. Understanding these interactions during ultrafast laser ablation requires detailed measurements of material properties and structural changes with high temporal and spatial resolutions. Traditional spatiotemporal imaging techniques relying on reflective imaging often fail to capture comprehensive information, resulting in predominantly qualitative theoretical models of these interactions. To overcome this limitation, we propose a dual-modal ultrafast microscopy system that combines two-dimensional reflectivity and three-dimensional topography imaging. By integrating pump-probe techniques with an interferometric imaging system, impressive spatiotemporal resolutions of 236 nm and 256 fs were achieved. Furthermore, using this system, we successfully examined the dynamics of laser-induced periodic surface structure formation, strengthening, and erasure on Si surfaces. The results demonstrate that the dual-modal spatiotemporal imaging technique can serve as a robust tool for the comprehensive analysis of ablation dynamics, facilitating a deeper understanding of the fundamental physics involved and enabling more accurate optimisation of ultrafast laser fabrication processes.